MnCo2O4/Mn2O3 Nanorod Architectures as Bifunctional Electrocatalyst Material for Rechargeable Zinc-Air Batteries - Ayyaluri, Ramakrishna Reddy; Vamsi Krishna, B. N.; Ankinapalli, Obula Reddy; Lee, Young Jun; Natarajan, Logeshwaran; Yu, Jae Su (American Chemical Society, 2024)
Recently, the demand for stable, cost-effective, and highly active bifunctional catalysts has increased in the energy storage community. In this study, we present the preparation of manganese cobalt oxide/manganese oxide (MnCo2O4/Mn2O3) nanorod (NR) materials via a facile one-step hydrothermal method without calcination. The MnCo2O4/Mn2O3 NR revealed better electrocatalytic properties toward the oxygen reduction and oxygen evolution reactions. The MnCo2O4/Mn2O3 NR electrocatalyst exhibited high diffusion-limiting current density values and greater durability compared to the Pt/C and IrO2 catalysts, respectively. The electrode material showed excellent chronopotentiometric stability for 30 h at 10 mA cm(-2) and displayed remarkable stability at different current densities with low potential drops. Furthermore, the MnCo2O4/Mn2O3 NR-based zinc-air battery (ZAB) exhibited a slightly smaller voltage plateau as well as lower electrochemical impedance values than the Pt/C//IrO2-based ZAB. Significantly, the MnCo2O4/Mn2O3 NR-based ZAB (68 cycles @ similar to 20.3 h) demonstrated better durability than the Pt/C//IrO2-based ZAB (28 cycles @ similar to 8.3 h). The obtained excellent bifunctional catalytic properties and cycling stability results indicate that MnCo2O4/Mn2O3 NRs are cheap and promising bifunctional catalyst candidates for rechargeable metal-air batteries.